Optimization of production planning and control in a clothing industry through lean manufacturing - Mesquita, Thaysa; Araújo, Patrícia Dias (Brazilian Journal of Production Engineering, 2025)
This article presents a case study on the application of Lean Manufacturing to optimize Production Planning and Control (PPC) in a clothing industry. The research was conducted in a company in the sector, which faced challenges related to long lead times, high demand variability and low flexibility in production processes. Given the competitiveness of the market, several businesses have sought to standardize and improve the predictability of their businesses. Companies seek characteristics that allow them to obtain good results compared to the competition. A proposal for improving business forecasting is presented by analyzing the process and identifying solutions with the principles of Lean Manufacturing. Tools such as value stream mapping, implementation of kanbans and reorganization of the factory layout were applied. The results obtained after implementing Lean Manufacturing were significant, allowing productivity gains and cost reductions with improved indicators. There was a 30% reduction in production lead times, a 20% decrease in in-process inventories and a 25% improvement in production flexibility to meet demand variations.
Keywords: Lean Manufacturing; PCP; Optimize; ERP; Confection